The impact of the Ethiopian health extension program and health development army on maternal mortality: A synthetic control approach. (July 2019) - Rieger, Matthias; Wagner, Natascha; Mebratie, Anagaw; Alemu, Getnet; Bedi, Arjun
Abstract: The Ethiopian government has implemented nationwide strategies to improve access to basic health services and enhance health outcomes. The Health Extension Program (HEP) launched in 2003, expanded basic health infrastructure and local human resources. In 2011, the government introduced the Health Development Army (HDA). HDA is a women-centered community movement inspired by military structures and discipline. Its special objective is to improve maternal health outcomes. This paper uses a synthetic control approach to assess the effects of HEP and HDA on maternal mortality ratios (MMR). The MMR data are from the Global Burden of Diseases (GBD) database. A pool of 42 Sub-Saharan African countries, covering the period 1990 to 2016, is used to construct a synthetic comparator which displays a mortality trajectory similar to Ethiopia prior to the interventions. On average, since 2004, maternal mortality in the control countries exhibits a moderate downward trend. In Ethiopia, the downward trend is considerably steeper as compared to its synthetic control. By 2016, maternal mortality in Ethiopia was lower by 171 (p-value 0.048) maternal deaths per 100, 000 live births as compared to its synthetic control. Between 2003 and 2016, Ethiopia's maternal mortality ratio declined from 728 to 357. These estimates suggest that a substantial proportion of this decline may be attributed to HEP/HDA. The Ethiopian experience of enhancing nation-wide access to and use of maternal health services in a short time-span is remarkable. Whether such a model may be transplanted is an open question. Highlights: Evaluates Ethiopia's Health Extension Program(HEP) and Health Development Army(HDA). Uses synthetic control models to assess effects on aggregate, maternal mortality ratios. Employs a weighted pool of 42 SSA countries (1990–2016) to construct a counterfactual. Finds that a substantial proportion of declines in MMR may be attributed to HEP/HDA.